2020
DOI: 10.4103/jehp.jehp_650_20
|View full text |Cite
|
Sign up to set email alerts
|

Social influence of COVID-19: An observational study on the social impact of post-COVID-19 lockdown on everyday life in Kerala from a community perspective

Abstract: BACKGROUND: The current novel coronavirus pandemic started as a simple outbreak in December 2019 from Wuhan, China, and it has now become a global threat. The governments from most of the countries including India have already taken strict precautionary measures to reduce the coronavirus spread such as social distancing, closure of schools, colleges, airports, restaurants, shopping malls, and other places where the people might gather. An increase in the levels of anxiety, aggression, depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A survey on Albanian residents and expats reported a high satisfactory rate (88.0%) on infection prevention and control measures against COVID-19 ( Kamberi, 2020 ). Likewise, an Indian survey from Kerala region revealed that 95% respondents were respectful of social restrictions imposed by the local government to tackle the current pandemic ( Saji, 2020 ). By contrast, United Kingdom residents were less satisfied with risk reduction measures implemented against COVID-19, especially with bans affecting business activities, with 31.1% interviewees convinced that quarantine could cause health problems, independently from the country of residence ( Saji, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A survey on Albanian residents and expats reported a high satisfactory rate (88.0%) on infection prevention and control measures against COVID-19 ( Kamberi, 2020 ). Likewise, an Indian survey from Kerala region revealed that 95% respondents were respectful of social restrictions imposed by the local government to tackle the current pandemic ( Saji, 2020 ). By contrast, United Kingdom residents were less satisfied with risk reduction measures implemented against COVID-19, especially with bans affecting business activities, with 31.1% interviewees convinced that quarantine could cause health problems, independently from the country of residence ( Saji, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the global COVID-19 brought great changes to all walks of life [1]. The future world will be rewritten by the pandemic, just like the Spanish influenza, influenza, smallpox, cholera, atypical pneumonia and other pandemics that the world suffered in the past 100 years or so, which had a huge impact on society [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…While the effect of mobile phone usage is well-documented,[ 28 ] the effect seen in this study can be due to the effect of social media misinformation, and in turn, can impact the students' risk perception. [ 3 29 ]…”
Section: Discussionmentioning
confidence: 99%